2012
DOI: 10.3109/17453674.2012.704563
|View full text |Cite
|
Sign up to set email alerts
|

Guideline on anterior cruciate ligament injury

Abstract: The Dutch Orthopaedic Association has a long tradition of development of practical clinical guidelines. Here we present the recommendations from the multidisciplinary clinical guideline working group for anterior cruciate ligament injury.The following 8 clinical questions were formulated by a steering group of the Dutch Orthopaedic Association.What is the role of physical examination and additional diagnostic tools?Which patient-related outcome measures should be used?What are the relevant parameters that infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 79 publications
4
80
0
2
Order By: Relevance
“…This supports previous studies that have identified activity demands and instability as important factors [1820]. Orthopaedic surgeons considered that a physically demanding occupation was a very important factor for recommending surgery (grading “3” twice as many times compared to “2”).…”
Section: Discussionsupporting
confidence: 87%
“…This supports previous studies that have identified activity demands and instability as important factors [1820]. Orthopaedic surgeons considered that a physically demanding occupation was a very important factor for recommending surgery (grading “3” twice as many times compared to “2”).…”
Section: Discussionsupporting
confidence: 87%
“…They recommended the use of a combination of physical examination using Lachman, pivot shift and anterior drawer tests, level 1 evidence, together with the following outcome scores-International Knee Documentation Committee Subjective Knee Evaluation Form Score (IKDC), Knee Injury and Osteoarthritis Outcome Score (KOOS) or Tegner Score from level 2 evidence [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients that are active in pivoting sports are more likely to successfully return to the initial sport when treated by ACL reconstruction as compared with conservative therapy [12, 13]. Furthermore, ACL reconstruction is recommended if patients complain of knee instability in common daily activities and work [14]. Optimal timing for an ACL reconstruction is when the range of knee motion has normalized and the synovial reaction in the knee has diminished [2, 12, 14].…”
Section: Introductionmentioning
confidence: 99%